Multi-criteria sustainability assessment of energy resources in the energy supply chain of smart city ecosystems - F. Bandeiras; Á. Gomes; M. Gomes; P. Coelho (Energy Nexus)
With most of the population living in cities, achieving a sustainable state of urban development in line with global objectives is critical to alleviate energy poverty and security issues. Smart cities should incorporate a selection of energy resources capable of improving urban sustainability. This selection can be based on assessments using economic, social, and environmental criteria. However, these assessments are usually limited in the number of indicators and energy resources assessed, often overlooking socio-economic/cultural aspects or less mature options. Therefore, this work provides a literature review and contributes a comprehensive sustainability assessment of energy efficiency measures and energy supply and storage technologies. The novelty lies in the large selection of individual measures, integration of emerging technologies, and incorporation of socio-economic/cultural criteria at larger societal scales. Moreover, the assessment relied on the weighted sum model with equal weighting, which enables results to be easily replicated or complemented with new data and applied to different policy scenarios. The robustness of the ranking results is evaluated through a sensitivity analysis by modifying dimension weights according to economic, social, and environmental scenarios. Results show LED lighting, ocean energy, and Ni-Cd batteries to be the best performing options in terms of overall sustainability in their respective fields independently of weight variations. Upon changing dimension weights, Pb-A batteries and pumped hydro energy storage become the best performing energy storage technologies in the social and environmental scenarios, respectively. Finally, potential challenges and limitations of sustainability assessments are addressed along with policy implications and recommendations for regulatory frameworks.